Controlling of logistics in production enterprises with separated processes of logistics in the context of empirical research - Bełch, Paulina; Bełch, Paweł (Controlling logistyki w przedsiębiorstwach produkcyjnych z wyodrębnionymi procesami logistycznymi w kontekście badań empirycznych, 2020)
The article presents selected research results regarding the conditions for controlling of logistics processes in manufacturing enterprises. The research goal was to determine the relationship between the occurrence of such controlling and the separation of logistics processes in enterprises. The research issues undertaken determined the choice of research methods, such as literature review and survey research. The implementation of logistics controlling is associated with the isolation of logistics processes, as evidenced by the result of the Chi2 independence test. This means that in process-oriented enterprises there is logistic process controlling. Logistics controlling is a broader concept, covering logistics in functional terms at every level of the institutional criterion, both micrological, metalogistic and macrological
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 131-140
Keywords: controlling of logistics processes; controlling of logistics; controlling of processes; manufacturing company; logistics processes; controlling procesów logistycznych; controlling logistyki; controlling procesów; przedsiębiorstwo produkcyjne; procesy logistyczne